PARENT-ASSISTED MODULAR READING PROGRAM: ITS EFFECT ON READING PERFORMANCE DURING THE COVID-19 PANDEMIC OF GRADE 5 PUPILS OF BIWAG ELEMENTARY SCHOOL, TALLAG CABAGAN ISABELA - Buncag, Rona (International Journal of Arts, Sciences and Education, 2022)
This study was conducted in order determine the effectiveness of the Parent-Assisted Modular Reading program among the 32 frustration readers in the grade 5 of Biwag Elementary School. The researcher made use of one group pre-test and post-test research design to determine the effectiveness of the program. After a thorough analysis, the results showed that reading performance of grade 5 students improved from a frustration reading level to a majority of Instructional readers with a few as independent readers. This demonstrates that the program was effective in improving the learners' reading skills. The findings were supported by a t-test analysis where the computed p-value is 0.0004 which is lesser than the alpha of 0.05, which revealed a significant difference in the learners' reading comprehension performance before and after the experiment. Additionally, grade 5 participants' reading speed increased, shifting from a preponderance of slow readers to a predominance of ordinary readers and a few quick readers. This demonstrates that the training was successful in enhancing the readers' ability to recognize words. The statistical analysis showing that the p-value is 0.0072 and the alpha of 0.05, supported this, demonstrating a substantial difference in the respondents' reading speed before and after the Parent-Assisted Modular Reading Program was implemented. As a result, the program is suggested for schools with struggling readers, as it has proven to be helpful in boosting reading skills.